A Platform for Web Augmentation Requirements Specification - Firmenich, Diego Andrés (2014)
Web augmentation has emerged as a technique for customizing Web applications beyond the personalization mechanisms natively included in them. This technique usually manipulates existing Web sites on the client-side via scripts (commonly referred as userscripts) that can change its presentation and behavior. Large communities have surfaced around this technique and two main roles have been established. On the one hand there are userscripters, users with programming skills who create new scripts and share them with the community. On the other hand, there are users who download and install in their own Web Browsers some of those scripts that satisfy their customization requirements, adding features that the applications do not support out-of-the-box. It means that Web augmentation requirements are not formally specified and they are decided according to particular userscripters needs. In this paper we propose CrowdMock, a platform for managing requirements and scripts. The platform allows users to perform two activities: (i) specify their own scripts requirements by augmenting Web sites with high-fidelity mockups and (ii) upload these requirements into an online repository. Then, the platform allows the whole community (users and userscripters) to collaborate improving the definition of the augmentation requirements and building a concrete script that implements them. Two main tools have been developed and evaluated in this context. A client-side plugin called MockPlug used for augmenting Web sites with UI prototype widgets and UserRequirements, a repository enabling sharing and managing the requirements.